NEW RECORDS OF HELEOMYZIDAE FOR ITALIAN FAUNA (Diptera) - Lo Giudice, Giuseppe; Rivosecchi, Leo (Fragmenta entomologica, 2010)
Some faunistic records of Heleomyzidae for italian fauna are provided. Six of the species Oldenbergiella seticerca Papp, 1980, Orbellia myopiformis Robineau-Desvoidy, 1830, Eccoptomera inermis Czerny, 1924, Neoleria flavicornis (Loew, 1862), Acantholeria vockerothi (Hackman, 1969), Gymnomus mariei (Séguy, 1934) and the genera Oldenbergiella and Orbellia are new for italian fauna.